Sistem Pendukung Keputusan Penentuan Kualitas Biji Kopi paada KBQ Baburrayyan Menggunakan Metode Topsis - Wahyuni Fitri (Yayasan Kita Menulis, 2019)
Coffee beans are beans from coffee plants and are a source of coffee drinks. There are several criteria that need to be considered in determining the quality of coffee beans. These criteria are water content, dirt, seed size, seed color, aroma of seeds, and live insects that are required in determining the quality of coffee beans. One method that can be used to solve problems in determining the quality of coffee beans is the TOPSIS (Technique for Order Preference by Similiarity to Ideal Solution) method. The TOPSIS method is a multi-criteria decision making method that uses the principle that the chosen alternative must have the shortest distance to the positive ideal solution and the farthest distance to the negative ideal solution. The steps used in the TOPSIS method are the normalization matrix calculation process, the weighted normalization matrix calculation process, the process of determining positive ideal solutions and negative ideal solutions, the process of calculating the distance of each alternative to the ideal solution, and the process of calculating the preference value of each alternative. The results of the TOPSIS method calculation process are information on determining the quality of coffee beans.